Effect of information on consumers' sensory evaluation of beef, plant-based and hybrid beef burgers. (March 2022) - Grasso, Simona; Rondoni, Agnese; Bari, Rehana; Smith, Rachel; Mansilla, Natalia
Highlights: First sensory evaluation of beef vs plant-based vs hybrid burger (60:40 beef - veg). 99 UK consumers assessed the burgers under blind, expected and informed conditions. In the blind condition the hybrid burger scored highest for overall liking. Informed purchase intent was higher for hybrid burgers than plant-based burgers. Informed max WTP was similar for beef and hybrid burgers and higher than plant-based. Abstract: This study assessed the effect of providing information on the consumers' sensory evaluation of three burgers: 100% beef, 100% plant-based and a hybrid (60% beef and 40% vegetables). A total of 99 UK consumers with balanced age and gender were recruited. Consumers assessed the burgers under blind, expected and informed conditions and answered questions on liking, Check-all-that-apply (CATA), willingness to buy (WTB) and willingness to pay (WTP). In addition, under blind and informed conditions, consumers were asked to indicate their likes and dislikes about each sample. Results show that consumers are positive towards hybrid burgers, in terms of overall acceptability, purchase intent, WTP and subjective comments. Hybrid meat products could represent an effective way for consumers to lower their meat consumption without compromising too much on the sensory quality and could represent a transition product to a more plant-based diet. These results are valuable and should inform future marketing, labelling and reformulation efforts of new hybrid meat product launches.